Ultra wideband microwave multi-port reflectometer in microstrip-slot technology: operation, design and applications - Seman, Norhudah (In-Teh, 2010)
A microwave reflectometer is an instrument to measure a complex ratio between reflected and incident waves at an input port of a uniform transmission line terminated in a Device Under Test (DUT). The conventional reflectometer is formed by a four-port network with two ports connected to a microwave source and DUT, and the remaining ports coupled to a heterodyne receiver which acts as a Complex Ratio Detector (CRT). By using the heterodyne receiver technique, the two microwave signals are converted in the linear manner to an Intermediate Frequency (IF) of hundreds of kHz where they are processed using digital means. The use of the heterodyne technique enables a very large dynamic range of 100 dB or more for this type of reflectometer. However, as the ratio of two original microwave signals has to be preserved at IF, a very advanced electronic circuitry is required to accomplish the linear conversion process. This complicated electronics leads to a large size of the conventional reflectometer and its high price tag. Many applications require compactsize and low-cost reflectometers. They can be built using N-port networks, with N being greater than 5, equipped only in scalar (power) detectors. This chapter describes the concept of a multi-port reflectometer which employs scalar instead of complex ratio detector to determine the complex reflection coefficient of DUT. It is shown that such a device requires a suitable calibration and mathematical transformations of the measured power at selected ports of the N-port to obtain the complex reflection coefficient of DUT. Because of this requirement, the multi-port reflectometer uses a computer to perform calibrations and measurements. The use of a computer accelerates the calibration and measurement procedure and at the same time it does not create a considerable overhead to the total cost of this measurement instrument. The challenge is to obtain a low-cost fully integrated N-port network operating over an ultra wide frequency band, which can be used to develop a fully operational reflectometer. This challenge is addressed in the present chapter. Practical configurations of this measurement instrument are described and the design of a compact fully integrated N-port network in microstrip-slot technique to build a reflectometer operating over an ultra wide microwave frequency band of 3.1 to 10.6 GHz is given.